2015
DOI: 10.5535/arm.2015.39.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Magnetic Resonance Imaging of the Neck and Its Usefulness in Management of Congenital Muscular Torticollis

Abstract: ObjectiveTo quantify magnetic resonance imaging (MRI) findings of congenital muscular torticollis (CMT) and to demonstrate the usefulness of quantitative MRI findings in the management of CMT.MethodsThis was a retrospective study of 160 subjects with CMT who had undergone neck MRI at the age of 48 months or younger at a tertiary medical center. Among the 160 subjects, 54 had undergone surgical release of CMT and 106 subjects had not undergone surgery. For the quantitative analysis, the ratios of area and inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…After remission of swelling of the affected SCM, even if atrophic or hyperechogenic changes of SCM muscle are found, their presence alone is not sufficient to confirm the diagnosis. Moreover, if subjects are hesitant to undergo surgery, MRI is used to determine the necessity for operation [ 21 ]. Because most of our subjects were diagnosed after 5 years of age and could be operated upon, MRI was used mainly for diagnosis of CMT, with all enrolled patients undergoing MRI before surgical release.…”
Section: Discussionmentioning
confidence: 99%
“…After remission of swelling of the affected SCM, even if atrophic or hyperechogenic changes of SCM muscle are found, their presence alone is not sufficient to confirm the diagnosis. Moreover, if subjects are hesitant to undergo surgery, MRI is used to determine the necessity for operation [ 21 ]. Because most of our subjects were diagnosed after 5 years of age and could be operated upon, MRI was used mainly for diagnosis of CMT, with all enrolled patients undergoing MRI before surgical release.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained by Kim et al demonstrated that CMT is more frequently associated with the left SCM muscle [ 41 ]. In this study, with a small difference, there were more cases of left-sided torticollis ( n = 57; 51%) than right-sided torticollis ( n = 54; 49%).…”
Section: Discussionmentioning
confidence: 99%
“…In future, better understanding of this 3D deformity using specialized imaging techniques and measurements can render assessments more objective and reproducible and hopefully may improve treatment outcomes. 6 14 36 …”
Section: Discussionmentioning
confidence: 99%